Occurrence, Toxic Equivalency and Human Health Risk Assessment of Dioxin-like and Non-Dioxin-Like Polychlorinated Biphenyls in Sanitary Pads Produced in Nigeria - Oladapo, Francis (FUDMA Journal of Sciences, 2026)
Dioxins and polychlorinated biphenyls (PCBs) are persistent organic pollutants recognised for their environmental persistence, bioaccumulative potential, and adverse toxicological effects. Despite the association of PCBs with chemical contamination in consumer products, limited information exists on their occurrence in feminine hygiene products. This study investigated the occurrence, toxicity equivalency (TEQ), and potential health risks associated with PCB congeners in sanitary pads produced in Nigeria. Six brands were randomly purchased from retail outlets in Lagos, Abuja, and Porthacourt. Samples were extracted in a mixture of hexane and acetone and analysed using gas chromatography coupled with mass spectrometer. Ten PCB congeners were detected across all brands, with total concentrations ranging from 0.0102 to 0.3200 ng.g-1. Two-way Analysis of Variance (ANOVA) indicated significant variability in sanitary pad brands, PCB congener type, and interactions between the two (p
Keywords: Dioxins; PCB Congeners; Toxic Equivalency; Sanitary Pads; Human Health Risk; Nigeria